A comparison study of aliphatic and aromatic structure directing agents influencing the crystal and electronic structures, and properties of iodoplumbate hybrids: water induced structure conversion and visible light photocatalytic properties1. Issue 28 (28th July 2015) - Liu, Guang-Ning; Shi, Jian-Ru; Han, Xiao-Jiang; Zhang, Xiao; Li, Ke; Li, Jie; Zhang, Tao; Liu, Qi-Sheng; Zhang, Zhen-Wei; Li, Cuncheng
<x xml:space="preserve">Abstract</x> This work discloses the different roles of aliphatic and aromatic cations as structure directing agents.